2020
DOI: 10.1016/j.jeoa.2020.100277
|View full text |Cite
|
Sign up to set email alerts
|

Are homeownership patterns stable enough to tap home equity?

Abstract: is to produce first-class research and forge a strong link between the academic community and decision-makers in the public and private sectors around an issue of critical importance to the nation's future. To achieve this mission, the Center sponsors a wide variety of research projects, transmits new findings to a broad audience, trains new scholars, and broadens access to valuable data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As people move through their middle and later years, there is a tension between 'ageing in place' and 'making a change'. Many older people remain in their home through their later years; a study in America found that 53% stayed in the home they owned in their 50s (Munnell et al 2020). Others would consider changing home (usually to 'downsize') but would prefer to live in the same community where they have existing social connections (Wiles et al 2012).…”
Section: Older Adults Ageing In Placementioning
confidence: 99%
“…As people move through their middle and later years, there is a tension between 'ageing in place' and 'making a change'. Many older people remain in their home through their later years; a study in America found that 53% stayed in the home they owned in their 50s (Munnell et al 2020). Others would consider changing home (usually to 'downsize') but would prefer to live in the same community where they have existing social connections (Wiles et al 2012).…”
Section: Older Adults Ageing In Placementioning
confidence: 99%
“…A recent study examined the stability of homeownership, precisely to assess whether borrowing against home equity is a reasonable option (Munnell et al 2020), using data from the 1992-2016 waves of the Health and Retirement Study (HRS). To describe the typical housing trajectories of people in their 50s until death required the creation of a synthetic cohort, 'splicing' together two cohorts to create a complete picture of late-life housing trajectories.…”
Section: Program Participationmentioning
confidence: 99%
“…Sequence groups for home-owning households in the synthetic cohort, 1992-2016.Source:Munnell et al (2020).…”
mentioning
confidence: 99%